Rapid Response to the Combination of Lenvatinib and Pembrolizumab in Patients with Advanced Carcinomas (Lung Adenocarcinoma and Malignant Pleural Mesothelioma) - Shalata, Walid (Cancers (Basel), 2021)
SIMPLE SUMMARY: Over the past decades, the multi-drug approach for treating various types of cancers was highly recommended. The aim of this study was to demonstrate the advantage of treating different carcinoma types with several combinations of immune checkpoint inhibitors (ICIs) and tyrosine kinase inhibitors (TKIs). We showed that patients treated with the combination of lenvatinib and pembrolizumab showed an enhanced response to therapy compared to other treatments. Our ex-vivo studies exhibited reduced proliferation and PD-L1 levels for PDX explants treated with this combination compared to untreated explants or those treated with a single treatment. Based on the results of this study, we propose that the combination of levatinib and pembrolizumab shows great potential as a treatment option for patients with non-small cell lung carcinoma and malignant pleural mesothelioma, as previously suggested by recent clinical trials. ABSTRACT: The new era of cancer treatments has made immune checkpoint inhibitors (ICIs) and emerging multikinase inhibitors (TKIs) the standards of care, thus drastically improving patient prognoses. Pembrolizumab is an anti-programmed cell death-1 antibody drug, and lenvatinib is a TKI with preferential antiangiogenic activity. We present, to our knowledge, the first reported series of cases consisting of patients with metastatic non–small cell lung cancer and malignant pleural mesothelioma who were treated with several types of chemotherapy combinations and ICIs followed by disease progression. They were subsequently treated with combined immunotherapy and TKI treatment, resulting in a near complete response within a very short time. Clinical responses were supported by in vitro testing of each patient’s lymphocytic response to pembrolizumab after pre-exposure of target cancer cells to lenvatinib.